Back Cover: Glycine Attenuates Citrobacter rodentium‐Induced Colitis by Regulating ATF6‐Mediated Endoplasmic Reticulum Stress in Mice. Issue 15 (6th August 2021) - Zhang, Yunchang; Jiang, Da; Jin, Yuhang; Jia, Hai; Yang, Ying; Kim, In Ho; Dai, Zhaolai; Zhang, Jinhua; Ren, Fazheng; Wu, Zhenlong
Abstract : Mol. Nutr. Food Res . 2021, 65, 2001065 DOI: 10.1002/mnfr.202001065 Citrobacter rodentium ( C. rodentium ) is a well described murine pathogen that closely resembles human diarrheal pathogens enteropathogenic Escherichia coli ( E. coli .) and enterohaemorrhagic E. coli . Adherent C. rodentium adapt to the gastrointestinal environment and undergo a virulence switch that facilitates colonization of the distal colon. The virulence proteins produced by C. rodentium lead to breakdown of the intestinal tight junction proteins and apoptosis of the intestinal epithelial cells, which enables permeation of C. rodentium into the lamina propria. Recognition of C. rodentium by the lamina propria immune cells initiates the mucosal inflammatory responses, including of secretion of pro‐inflammatory cytokines and infiltration of immune cells themselves in the colonic epithelium. Supplementation with glycine restores the integrity of the colonic epithelium by upregulating tight junction protein expression and inhibiting of intestinal epithelial cell apoptosis, thus suppressing the overactivated inflammatory responses. Supplementation with glycine is a nutritional strategy to alleviate C. rodentium ‐induced colitis in mice. This is reported by Zhenlong Wu and co‐workes in article number 2001065 .